The Consumption of Exotic Fruits and Vegetables in the City of Zadar - Galić, Antonijo; Gauta, Bruno; Halilović, Lidija; Jadreško, Ivana; Kardum, Suzana (Oeconomica Jadertina, 2017)
Consumers in Croatia only recently got the opportunity to buy exotic fruits and vegetables. Until now offer was limited to the already known species which could be found on the shelves for decades, and this types can generally be cultivated in Croatia (except bananas, pineapples and several types of citrus). The demand for exotic fruits and vegetables and its cultivation in Western Europe is growing, and this trend is coming to Croatia. In the study conducted for the city of Zadar the correlation of the interest in buying exotic fruit/vegetables and familiarity with the product, the exact definition of the product and the most significant characteristics of kiwano/sweet potatoes was explored. Regression analysis results showed that all three independent variables significantly predict purchase of both kiwano and sweet potatoes. Three segments of consumers with respect to their demographic characteristics were identified using cluster analysis. A more detailed analysis of these groups could serve future researchers in order to segment the market and determine the marketing approach to each of the segments.
Keywords: exotic fruit; exotic vegetables; consumption; kiwano; sweet potato; cluster analysis